Studies on aspects of the chemotherapeutic control of the salmon louse Lepeophtheirus salmonis Kroyer 1837 (Copepoda: Caligidae). - Roth, Myron (1992)
The efficacy of a range of anti-parasitic chemotherapeutic agents against the salmon louse Lepeophtheirus salmonis following topical application was studied in vitro and in vivo. In general, adult and preadult lice were susceptible to a wide range of compounds with dose rates, following 1 hour exposures, ranging several orders of magnitude (10.0 - 0.001 mg/L). Overall the pyrethroid compounds which were tested were found to have the widest therapeutic ratios, indicating the potential of this group of chemotherapeutants for sea lice control. Resistance to the organophosphorus (OP) compounds dichlorvos and azamethiphos was detected in isolated populations of lice. Field trials with azamethiphos indicated that the compound was highly efficacious against sensitive lice (@ 0.1 mg/L; however, where resistance was present, efficacy (@ 0.2 mg/L) was highly variable. When used at the above dose rates, azamethiphos was found to be well tolerated by fish as indicated by a lack of significant brain acetylcholinesterase inhibition. Results on cross resistance (between pyrethroids and OPs) were inconclusive which was believed to be, primarily, due to the overall high toxicity of the group; but also to the variable responses from exposed lice. In a series of preliminary trials, one of the pyrethroid compounds, PHRDL-D, was found to effectively remove lice when administered orally to infected salmon, indicating the potential of pyrethroids as oral chemotherapeutants. A comparison of the relative toxicity of azamethiphos (OP), resmethrin (pyrethroid), ivermectin (avermectin) and the structurally similar compound SKB7 (milbemycin), indicated that chalimus stages were only susceptible to ivermectin and SKB7 following topical and intra-peritoneal injection to lice infected fish. In contrast, azamethiphos and resmethrin were found to be non toxic to chalimus larvae at dose rates which were highly toxic to both adult lice and treated fish. Preliminary studies on the uptake of r4C]azamethiphos in adult lice indicated that uptake was ...